(519) Special Conceptions of Socialist Economy: (Part 2) Conceptions of Economic Categories المفاهيم الخاصة بالاقتصاد الاشتراكي: (الجزء الثاني) مفاهيم الفئات الاقتصادية - Linsel, Hermann; Sack, Kurt (INP, 2024)
Conceptions of Cost, Credit, Price, and Return in the Socialist Economy|, Prime Cost Prime cost includes: The value of fixed capital used in the production process (depreciations, rents, and leases). The value of working capital used (materials) and external services. Wages paid to enterprise workers involved in: Material supply. Product production. Product marketing. Reduction of Prime Cost, Reduction of prime cost refers to producing a certain product with at least equal quality while saving fixed and working capital. The total reduction in prime cost is calculated as: The difference between the total prime cost of comparable commodity production (in the current period) and the total basic cost of the same output. Basic cost is determined by multiplying the comparable output of the current period by the prime cost of one production unit from the previous or basic period.